Fuego, fueguito = Fire, Little Fire = Tit, titchin [book with audioplayer] - Argueta, Jorge (VOX Books, 2021)
With stunningly beautiful illustrations by Felipe Ugalde Alcantara that depict the natural world, this poem about the importance of fire reflects Argueta's indigenous roots and his appreciation for nature. Containing the English and Spanish text on each page, the entire poem appears at the end in Nahuat, the language of Argueta's Pipil-Nahua ancestors. The sequel to Agua, Aguita / Water, Little Water, this book is an excellent choice to encourage children to write their own poems about the environment.